The invisibility and the possibility to adjust of the students with mild intellectual disabilities from the perspectives of lecturers in general classroom at University in Indonesia - Silvia Sembiring; Nopriansah Nopriansah; Nopal Kurniawansyah; Laula Hanna Maryam (UNIVED Press, 2020)
Although famous as a favorite junior high school, English is st ill a scourge for most students of universities. As a result, students' English learning achievement does not meet the KKM. The group investigation learning model is one alternative to improve student learning achievement. Classroom action research the stages of planning, implementing, observing, and reflecting on each cycle is used to improve this situation. Planning is carried out according to the results of the identification and reflection of the previous cycle. Implementation according to plan. Observations are emphasized on the implementation of learning, increasing learning achievement, and student responses. Reflections are made to make the necessary improvements so that learning objectives are achieved. The results showed that students have positive attitudes and responses to English learning with the group investigation model on the subject of English. English learning achievement of university students in 2019/2020 in the subject of English by using a group investigation model increased with an average value of 81.5 so that it was categorized quite well. Teachers can use the group investigation model as an alternative to improving students' English learning achievement. Keyword: Learning achievement, Learning model, Group investigation